COMMUNICATIVE MANAGEMENT AS A COMPONENT OF MAKING EFFECTIVE MANAGEMENT DECISIONS (Development Service Industry Management, 2025)
The article examines the role of communicative management as a key factor in the process of making managerial decisions. An effective managerial process largely depends on the quality of internal and external communications, therefore, their impact on the managerial process is considered. Properly organized internal and external communications ensure an effective managerial process, increase the competitiveness of the organization and contribute to its strategic development. It is proven that effective communication is the basis for making high-quality managerial decisions, as it provides access to important information, reduces the risks of misinterpretation of data, improves team interaction and promotes rapid response to changes. Effective communication promotes active interaction between managers and employees, which makes it possible to involve specialists in the decision-making process, receive alternative opinions and ideas, which helps to find the best solutions to problems, and form responsibility for the implementation of adopted decisions. The main problems of communication exchange associated with barriers to information perception and methods for overcoming them are identified. A classification of communication barriers has been developed. The impact of digital technologies, such as CRM systems, corporate portals and messengers, on improving communication processes has been analyzed. Modern digital communication management tools have been summarized, including Feedback Methods, Brainstorming and SWOT Analysis. It has been proven that high-quality communication contributes to quick decision-making, reducing the level of conflict and increasing staff productivity. It has been argued that the free exchange of information between departments and management levels contributes to the enrichment of the decision-making process and its greater diversity.
Keywords: communicative management; communication; managerial decision-making; internal and external communications; communication barriers